If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x) + ln(x + -7) = ln(18) Multiply ln * x lnx + ln(x + -7) = ln(18) Reorder the terms: lnx + ln(-7 + x) = ln(18) lnx + (-7 * ln + x * ln) = ln(18) lnx + (-7ln + lnx) = ln(18) Reorder the terms: -7ln + lnx + lnx = ln(18) Combine like terms: lnx + lnx = 2lnx -7ln + 2lnx = ln(18) Reorder the terms for easier multiplication: -7ln + 2lnx = 18ln Solving -7ln + 2lnx = 18ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-18ln' to each side of the equation. -7ln + -18ln + 2lnx = 18ln + -18ln Combine like terms: -7ln + -18ln = -25ln -25ln + 2lnx = 18ln + -18ln Combine like terms: 18ln + -18ln = 0 -25ln + 2lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(-25 + 2x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-25 + 2x)' equal to zero and attempt to solve: Simplifying -25 + 2x = 0 Solving -25 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 2x = 0 + 25 Combine like terms: -25 + 25 = 0 0 + 2x = 0 + 25 2x = 0 + 25 Combine like terms: 0 + 25 = 25 2x = 25 Add '-2x' to each side of the equation. 2x + -2x = 25 + -2x Combine like terms: 2x + -2x = 0 0 = 25 + -2x Simplifying 0 = 25 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 0.5k-0.75=k+2 | | -8=-3r+1 | | -8=-3r | | 3x^2-15x+186=0 | | (6x-3)/5=(4x-1)/3 | | 6(4r-3)(r+5)=0 | | 8r+1.75=20.25 | | 13x1/4 | | Y=(sin2x)/(cosx)-3cos(2x) | | (D^3+4D^2+6D+4)=x-sinx | | 5x+4=(x+5) | | (D^3+4D^2+6)=0 | | 3sin^2x-cosx=2 | | 5x+75=8x+40x-40 | | 6/x=60/70 | | 7-1/4c=6 | | (D^3-4D^2+D+6)=0 | | 3^3/1 | | -8(-1-2r)=104 | | 4(z-4)-3z= | | (x+2)(-3)=0 | | 4(4)-3=13 | | 3x+1=0.5x+10 | | 8(x-3)+1= | | dx+35=64 | | -9f=-45 | | X+25=53 | | 7(n+4)-5n=-6(n-6) | | x+4=-10x-6 | | 6x/2=2(5x-3) | | 8x^2-115x-115=0 | | -6(5r-7)=19-7r |